Development of a Single Nucleotide Polymorphism‐Based Genetic Identification Key for Date Palm Cultivars. Issue 6 (1st November 2019) - Faqir, Nadia; Muhammad, Aish; Ali, Ghulam Muhammad; Shehzad, Armghan; Ali, Kazim; Rahman, Hafeez Ur; Farhatullah,; Souza, Manoel Teixeira; Ali, Muhammad; Akhtar, Malik Nadeem; Hyder, Muhammad Zeeshan
ABSTRACT: Date palm ( Phoenix dactylifera L.) has a long history of cultivation and valuable germplasm in Pakistan, with little knowledge about its genetic makeup and diversity. The objective of this work was to develop a DNA sequence based genetic identification system for date palm cultivars. DNA fragments of rbcL (∼500 bp), atpB (∼500 bp) and 16S rRNA (∼1000 bp) genes of chloroplast genome and 12 DNA fragments from nuclear genome of seven cultivars were sequenced. Sequence analysis indicated that three fragments had higher marker index of 4.61, 3.61, and 2.26 with eight, seven, and five single nucleotide polymorphisms (SNPs), respectively. Eight novel SNP sites were also found in the sequenced fragments. Based on sequenced data, a SNP typing system was developed for varietal identification of date palm cultivars, using unique SNP signatures. To validate this system, the four highest SNP‐bearing fragments were sequenced from 30 additional date palm cultivars. The SNP data from these four fragments were able to resolve 70% of the cultivars with unique signatures. This strategy could be expanded to search more SNP sites and achieve improved resolution for identification of date palm germplasm.